Aspartic acid-based porous hard carbon material as well as preparation method and application thereof

By preparing aspartic acid-based porous hard carbon materials, the problems of low specific capacity and poor stability of hard carbon materials were solved, achieving high-capacity and stable sodium-ion battery anode performance, reducing raw material costs and simplifying the preparation process.

CN120903477APending Publication Date: 2025-11-07ENERGY RESOURCES INST HEBEI ACADEMY OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511216386.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing hard carbon materials used as anodes in sodium-ion batteries suffer from low specific capacity and poor stability, hindering their industrial application.

Method used

Aspartic acid-based porous hard carbon materials were prepared by grinding and high-temperature carbonization using aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate, and ammonium carbonate as raw materials, forming a carbon skeleton with high specific capacity and stability.

Benefits of technology

The prepared hard carbon material exhibits high discharge specific capacity and good electrochemical performance in sodium-ion batteries. After 1000 cycles under high current, the specific capacity can still be maintained at 88%, and the raw materials are widely available and inexpensive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of hard carbon materials, and provides an aspartic acid-based porous hard carbon material and a preparation method and application thereof.The preparation method comprises the following steps that A, aspartic acid, polyvinylpyrrolidone, rubber leftover materials, zinc chloride, magnesium sulfate and ammonium carbonate with the mass ratio of (3-7): (4-6): (3-7): (3-7): (1-3): (1-3) serve as raw materials, the raw materials are ground and mixed, then the temperature is increased to 400-600 DEG C, and a mixture is obtained; keeping the temperature for 2-4 hours to obtain a black brown carbon precursor; and B, grinding into powder, and carbonizing for 1-3 hours at the temperature of 1200-1500 DEG C in an inert gas atmosphere to obtain the hard carbon material. The hard carbon material has higher specific capacity and stability, and the preparation method of the hard carbon material is simple and easy to operate and has good application value.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of hard carbon materials, and relates to an aspartic acid-based porous hard carbon material and a preparation method and application thereof. BACKGROUND

[0002] Lithium ion batteries are widely concerned due to high energy density, long service life and environmental friendliness, but with the large-scale application of electric vehicles and energy storage power stations, the demand for lithium resources has also greatly increased. Lithium resource shortage and uneven distribution have also begun to appear, becoming a bottleneck problem restricting the development of lithium ion batteries. In contrast, sodium in sodium ion batteries, as a charge carrier energy storage, is in the same group as lithium, and has cost and resource advantages, making it the best substitute for lithium ion batteries. Among the many negative electrode materials available for sodium ion batteries, carbon negative electrodes have lower potential, higher capacity, stable physical and chemical properties, and low cost, and become the first choice for commercial development of sodium ion batteries. However, the current commercial graphite negative electrode material cannot be applied in sodium ion batteries, and its sodium storage capacity is too low, and the energy density is far from the existing commercial lithium ion batteries, so it is necessary to develop new carbon negative electrode materials.

[0003] Among various carbon materials, amorphous carbon materials show better performance. Amorphous carbon materials include soft carbon and hard carbon, and hard carbon as a negative electrode of sodium ion batteries has a higher specific capacity, and the large interlayer spacing and porous structure of hard carbon material can relieve the volume expansion during the reaction, which is beneficial to the commercialization of sodium ion batteries. However, hard carbon material as a negative electrode of sodium ion batteries also has some problems, such as low specific capacity and poor stability, which seriously hinder the industrialization application of hard carbon-based negative electrode materials.

[0004] The inventors have been committed to the research of hard carbon materials. For example, CN117023556A discloses a sodium battery negative material prepared from rubber scraps, a preparation method and application thereof. The method comprises the following steps: calcining rubber scrap powder and urea after first mixing to obtain a rubber scrap carbide; and sequentially drying and carbonizing the rubber scrap carbide and potassium hydroxide solution after second mixing to obtain a rubber scrap-based hard carbon, which is a sodium battery negative material. CN118239472A discloses a preparation method of a porous hard carbon material, which comprises the following steps: mixing phenolic resin, DL-aspartic acid, magnesium phosphate, potassium salt and ammonium salt by ball milling, and carbonizing the mixed sample at 900-1200°C for 0.5-5h in an inert gas atmosphere to obtain a phosphorus-doped porous hard carbon. CN118099421A discloses a phenolic resin-based hard carbon material for sodium ion batteries, which comprises the following steps: preparing a modified phenolic resin solid: adding hexachlorotriphosphazene to a phenolic resin solution, stirring uniformly at room temperature, then adding an organic base and continuing to stir, after that, adding m-benzene triol and continuing to stir for polymerization reaction to obtain a gel-like solidified product, and freeze-drying the gel-like solidified product to obtain the modified phenolic resin solid; and preparing a hard carbon material: mixing the prepared modified phenolic resin solid with sodium molybdate salt, and performing carbonization reaction in a nitrogen atmosphere furnace to obtain the hard carbon material. CN116715216A discloses a preparation method of a hard carbon with high specific surface area, which comprises the following steps: mixing DL-aspartic acid, potassium formate, polyvinylpyrrolidone, ammonium chloride and melamine by ball milling, and carbonizing the intermediate product at 1100-1300°C in an inert gas atmosphere for 0.5-5h, and then acid washing to obtain the hard carbon material. CN116199223A discloses a preparation method of a hard porous carbon, which comprises the following steps: ball milling biomass carbon material, pore-forming agent, nitrogen-containing sulfur compound and alkali to obtain a mixture; and performing carbonization reaction on the mixture to obtain a hard porous carbon for sodium ion batteries. CN118877876A discloses a phenolic resin-based hard carbon material, and the preparation method comprises: ball milling phenolic resin, zinc acrylate and potassium tripolyphosphate in a mass ratio of 2-10:0.5-5:1-8, and then performing carbonization in an inert gas atmosphere at 1300-1500°C for 1-5h to obtain the phenolic resin-based hard carbon material. The hard carbon materials prepared by the above methods all have excellent cycle stability, but the battery capacity is not high.

[0005] Therefore, it is of great value to develop a hard carbon material for sodium ion batteries, which has high specific capacity, good stability and simple preparation process. SUMMARY

[0006] The application provides aspartic acid-based porous hard carbon material and a preparation method and application thereof, the hard carbon material has higher specific capacity and stability, and the preparation method of the hard carbon material is simple, easy to operate, and has good application value.

[0007] The technical scheme of the application is as follows: Technical subject one The application provides a preparation method of aspartic acid-based porous hard carbon material, comprising the following steps: A. aspartic acid, polyvinylpyrrolidone, rubber offcut, zinc chloride, magnesium sulfate and ammonium carbonate are used as raw materials in a mass ratio of 3-7:4-6:3-7:3-7:1-3:1-3, after grinding and mixing, the temperature is increased to 400-600 DEG C, and the temperature is kept for 2-4 h to obtain a black-brown carbon precursor; B. then the powder is ground, and the hard carbon material is obtained by carbonizing at 1200-1500 DEG C for 1-3 h in an inert gas atmosphere.

[0008] The rubber offcut usually refers to vulcanized rubber waste rubber material generated in the production, processing and trimming process of rubber products and not used finally.

[0009] Specific forms: including but not limited to: cutting scraps, stamping offcuts, flash, burrs in the production process; unqualified products (defective products, scrap products); mold overflow (rubber edge).

[0010] Preferably, the rubber offcut is vulcanized natural rubber offcut.

[0011] Preferably, the average molecular weight of the polyvinylpyrrolidone is 8000.

[0012] Preferably, the step A is ground to 100-300 meshes.

[0013] Preferably, the step A is heated to 400-600 DEG C at a rate of 4-6 DEG C / min.

[0014] Preferably, the step B is ground to 100-200 meshes.

[0015] Preferably, the inert gas in the step B is selected from one of nitrogen, helium or argon.

[0016] Preferably, the carbonization process in step B specifically comprises: continuously passing inert gas at a rate of 5-10 mL / min, heating to 1200-1500℃ at a rate of 5-10℃ / min, and then maintaining for 1-3h, and naturally cooling to room temperature.

[0017] Preferably, after the carbonization in step B is completed, the method further comprises a washing and drying step.

[0018] Preferably, the washing step comprises: washing with a 5% hydrochloric acid solution, and then washing with anhydrous ethanol.

[0019] Preferably, the drying step comprises: vacuum drying at 100-110℃.

[0020] Preferably, the mass ratio of aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate is 5:5:5:5:2:2.

[0021] Preferably, the carbonization temperature in step A is 500℃. Preferably, the carbonization temperature in step B is 1350℃.

[0022] Technical subject two The application also provides an aspartic acid-based porous hard carbon material prepared by the preparation method of the aspartic acid-based porous hard carbon material.

[0023] Technical subject three The application also provides an application of the aspartic acid-based porous hard carbon material in a sodium ion battery.

[0024] The application has the following beneficial effects: 1. In the application, rubber scraps with low price are used to prepare hard carbon materials, which can reduce the raw material cost of sodium battery negative materials. In addition, the hard carbon material prepared by rubber scraps, aspartic acid, polyvinylpyrrolidone, zinc chloride, magnesium sulfate and ammonium carbonate has higher specific capacity and stability. When the hard carbon material prepared by the application is used as the negative electrode of a sodium ion battery, it has good electrochemical performance: the battery discharge specific capacity is as high as 378mAh / g, and the specific capacity after 1000 cycles at a large current of 10A / g is still as high as 88%.

[0025] 2. The preparation method provided by the application is simple to operate, the raw materials are widely available, simple and cost-saving, and has a high practical application prospect.

[0026] 3. In this invention, rubber scraps are used as a carbon skeleton. At high temperature, zinc chloride is used to etch out heteroatom functional groups, which react with aspartic acid and polyvinylpyrrolidone. At high temperature, aspartic acid can generate free radicals that polymerize with polyvinylpyrrolidone. Magnesium sulfate and zinc chloride have an etching effect at high temperature, and at the same time, magnesium and zinc are in-situ doped to improve the capacitance. Attached Figure Description

[0027] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0028] Fig. 1 This is a transmission electron microscope image of the hard carbon material in Example 1 of the present invention.

[0029] Fig. 2 This is a scanning electron microscope image of the hard carbon material in Example 1 of the present invention.

[0030] Fig. 3 XPS image of hard carbon material in Example 1 of this invention. Detailed Implementation

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless otherwise specified, the experimental or testing methods involved in the embodiments of this invention are conventional methods in the prior art, and their names and / or abbreviations are conventional names in the art, clearly defined in their respective fields of application. Those skilled in the art can understand the conventional process steps based on these names and apply the corresponding equipment, implementing them under conventional conditions or conditions recommended by the manufacturer. The various instruments, equipment, raw materials, or reagents used in the embodiments of this invention are not subject to any special restrictions on their source; they are all conventional products that can be purchased through legitimate commercial channels and can be prepared according to conventional methods well known to those skilled in the art.

[0033] The average molecular weight of polyvinylpyrrolidone is 8000.

[0034] Rubber scraps are scraps of natural rubber that have undergone vulcanization.

[0035] Example 1 A preparation method of aspartic acid-based porous hard carbon material, comprising the following steps: A, aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate are used as raw materials in a mass ratio of 5:5:5:5:2:2, the mixture is ground (ground to 200 mesh), heated to 500 DEG C at a rate of 5 DEG C / min, and a black-brown carbon precursor is obtained after 3h of heat preservation; B, then ground into powder (ground to 200 mesh), inert gas is continuously introduced at a rate of 8mL / min, heated to 1350 DEG C at a rate of 8 DEG C / min, carbonized for 1.5h, naturally cooled to room temperature, washed with 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105 DEG C to obtain the hard carbon material.

[0036] The hard carbon material obtained in Example 1 is characterized by TEM, SEM and XPS, as shown in Figs. 1-3 The figure shows that the surface of the hard carbon material obtained by the application is rich in wrinkles, as shown in Fig. 3 , which proves that zinc, sulfur and magnesium are successfully doped in the hard carbon material.

[0037] Example 2 A preparation method of aspartic acid-based porous hard carbon material, comprising the following steps: A, aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate are used as raw materials in a mass ratio of 4:6:4:7:1:3, the mixture is ground (ground to 100 mesh), heated to 400 DEG C at a rate of 6 DEG C / min, and a black-brown carbon precursor is obtained after 4h of heat preservation; B, then ground into powder (ground to 100 mesh), inert gas is continuously introduced at a rate of 10mL / min, heated to 1500 DEG C at a rate of 5 DEG C / min, carbonized for 1h, naturally cooled to room temperature, washed with 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 100 DEG C to obtain the hard carbon material.

[0038] Example 3 A preparation method of aspartic acid-based porous hard carbon material, comprising the following steps: A, aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate are used as raw materials in a mass ratio of 7:4:6:3:3:1, the mixture is ground (ground to 300 mesh), heated to 600 DEG C at a rate of 4 DEG C / min, and a black-brown carbon precursor is obtained after 2h of heat preservation; B, then ground into powder (ground to 200 mesh), inert gas was constantly introduced at a rate of 5 mL / min, the temperature was raised to 1200℃ at a rate of 10℃ / min, carbonized for 3h, naturally cooled to room temperature, washed with 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 110℃ to obtain the hard carbon material.

[0039] Example 4 A method for preparing aspartic acid-based porous hard carbon material, comprising the following steps: A, aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate were used as raw materials in a mass ratio of 5:4:4:4:3:2, and after grinding the mixture (ground to 200 mesh), the temperature was raised to 450℃ at a rate of 5℃ / min, and a black-brown carbon precursor was obtained after 3h of heat preservation; B, then ground into powder (ground to 100 mesh), inert gas was constantly introduced at a rate of 10 mL / min, the temperature was raised to 1400℃ at a rate of 10℃ / min, carbonized for 2h, naturally cooled to room temperature, washed with 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105℃ to obtain the hard carbon material.

[0040] Comparative Example 1 Compared with Example 1, the only difference is that aspartic acid is not added. It comprises the following steps: A, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate were used as raw materials in a mass ratio of 5:10:5:2:2, and after grinding the mixture (ground to 200 mesh), the temperature was raised to 500℃ at a rate of 5℃ / min, and a black-brown carbon precursor was obtained after 3h of heat preservation; B, then ground into powder (ground to 200 mesh), inert gas was constantly introduced at a rate of 8 mL / min, the temperature was raised to 1350℃ at a rate of 8℃ / min, carbonized for 1.5h, naturally cooled to room temperature, washed with 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105℃ to obtain the carbon material.

[0041] Comparative Example 2 Compared with Example 1, the only difference is that polyvinylpyrrolidone is not added. It comprises the following steps: A, aspartic acid, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate were used as raw materials in a mass ratio of 5.1:5:5:2:2, and after grinding the mixture (ground to 200 mesh), the temperature was raised to 500℃ at a rate of 5℃ / min, and a black-brown carbon precursor was obtained after 3h of heat preservation; B. Then, grind into powder (grind to 200 mesh), constantly pass in inert gas at a rate of 8 mL / min, increase temperature to 1350°C at a rate of 8°C / min, carbonize for 1.5 h, naturally cool to room temperature, wash 3 times with a 5% hydrochloric acid solution, then wash 3 times with anhydrous ethanol, and then vacuum dry at 105°C to obtain the carbon material.

[0042] Comparative Example 3 Compared with Example 1, the only difference is that magnesium sulfate is not added. The following steps are included: A. Aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, and ammonium carbonate are used as raw materials at a mass ratio of 5:5:5:5:2, and after grinding the mixture (grind to 200 mesh), increase the temperature to 500°C at a rate of 5°C / min, and obtain a black-brown carbon precursor after 3 h of heat preservation; B. Then, grind into powder (grind to 200 mesh), constantly pass in inert gas at a rate of 8 mL / min, increase temperature to 1350°C at a rate of 8°C / min, carbonize for 1.5 h, naturally cool to room temperature, wash 3 times with a 5% hydrochloric acid solution, then wash 3 times with anhydrous ethanol, and then vacuum dry at 105°C to obtain the carbon material.

[0043] Comparative Example 4 Compared with Example 1, the only difference is that ammonium carbonate is not added. The following steps are included: A. Aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, and magnesium sulfate are used as raw materials at a mass ratio of 5:5:5:5:2, and after grinding the mixture (grind to 200 mesh), increase the temperature to 500°C at a rate of 5°C / min, and obtain a black-brown carbon precursor after 3 h of heat preservation; B. Then, grind into powder (grind to 200 mesh), constantly pass in inert gas at a rate of 8 mL / min, increase temperature to 1350°C at a rate of 8°C / min, carbonize for 1.5 h, naturally cool to room temperature, wash 3 times with a 5% hydrochloric acid solution, then wash 3 times with anhydrous ethanol, and then vacuum dry at 105°C to obtain the carbon material.

[0044] Comparative Example 5 Compared with Example 1, the only difference is that the amount of aspartic acid added is different. The following steps are included: A. Aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate, and ammonium carbonate are used as raw materials at a mass ratio of 3:5:5:5:2:2, and after grinding the mixture, increase the temperature to 400-600°C, and obtain a black-brown carbon precursor after 2-4 h of heat preservation; B. Then, the mixture was ground into powder (ground to 200 mesh), inert gas was continuously introduced at a rate of 8 mL / min, and the temperature was raised to 1350°C at a rate of 8°C / min, carbonized for 1.5 h, and then naturally cooled to room temperature. The carbon material was obtained by washing with a 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105°C.

[0045] Comparative Example 6 Compared with Example 1, the only difference is that the amount of aspartic acid is different, including the following steps: A. Aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate were used as raw materials in a mass ratio of 8:5:5:5:2:2. After grinding and mixing, the temperature was raised to 400-600°C, and the black-brown carbon precursor was obtained after holding for 2-4 h; B. Then, the mixture was ground into powder (ground to 200 mesh), inert gas was continuously introduced at a rate of 8 mL / min, and the temperature was raised to 1350°C at a rate of 8°C / min, carbonized for 1.5 h, and then naturally cooled to room temperature. The carbon material was obtained by washing with a 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105°C.

[0046] Comparative Example 7 Compared with Example 1, the only difference is that aspartic acid is replaced by an equimolar amount of urea, including the following steps: A. Urea, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate were used as raw materials in a mass ratio of 2.26:5:5:5:2:2. After grinding and mixing (ground to 200 mesh), the temperature was raised to 500°C at a rate of 5°C / min, and the black-brown carbon precursor was obtained after holding for 3 h; B. Then, the mixture was ground into powder (ground to 200 mesh), inert gas was continuously introduced at a rate of 8 mL / min, and the temperature was raised to 1350°C at a rate of 8°C / min, carbonized for 1.5 h, and then naturally cooled to room temperature. The carbon material was obtained by washing with a 5% hydrochloric acid solution for 3 times, then washed with anhydrous ethanol for 3 times, and then vacuum dried at 105°C.

[0047] Performance test Preparation of working electrode: The hard carbon material prepared in the examples and comparative examples was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, and then N-methylpyrrolidone was added while grinding to prepare a slurry. The slurry was evenly spread on a copper box and heated and dried to obtain a working electrode.

[0048] Preparation of electrolyte: The electrolyte was a mixed solution of EC: DMC: EMC in a volume ratio of 1:2:2, and the concentration of solute NaPF6 was 1.5M.

[0049] Test: The glass microfiber separator, sodium metal sheet as reference electrode, working electrode, CR2032 battery shell, gasket were put into the glove box filled with argon to assemble into a half battery.

[0050] 1. The assembled button cell was tested by LAND CT2001A battery test system under a large current of 10A / g, and the stability refers to the capacity retention rate of the battery after 1000 cycles.

[0051] 2. Under the constant temperature condition of 25℃, 0.1C rate constant current discharge to 0V, the discharge capacity at this time was recorded as the first cycle (first) discharge capacity; continue to charge at 0.1C constant current to 2V, record the charge capacity at this time as the first cycle (first) charge capacity, record the charge capacity at this time as the first cycle (first) charge capacity; the first coulombic efficiency = the first cycle charge specific capacity / the first cycle discharge specific capacity * 100%.

[0052] The test results are shown in Tables 1-2.

[0053] Table 1 Table 2 The above is only the preferred embodiment of the present application, and is not used to limit the present application, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing an aspartic acid-based porous hard carbon material, characterized by, The method comprises the following steps: A. Aspartic acid, polyvinylpyrrolidone, rubber scraps, zinc chloride, magnesium sulfate and ammonium carbonate are used as raw materials in a mass ratio of 4-7:4-6:4-6:3-7:1-3:1-3, and after grinding and mixing, the temperature is raised to 400-600 DEG C and kept for 2-4 h to obtain a black-brown carbon precursor; B. Then, the mixture is ground into powder, and carbonized at 1200-1500 DEG C for 1-3 h in an inert gas atmosphere to obtain a hard carbon material.

2. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The rubber scraps are natural rubber scraps.

3. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The average molecular weight of the polyvinylpyrrolidone is 8000.

4. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The step A is ground to 100-300 mesh.

5. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The step A is heated to 400-600 DEG C at a rate of 4-6 DEG C / min.

6. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The step B is ground to 100-200 mesh.

7. The method for preparing an aspartic acid-based porous hard carbon material according to claim 1, characterized in that, The inert gas in the step B is selected from one of nitrogen, helium or argon.

8. The method of claim 1, wherein, The carbonization process in the step B specifically comprises: continuously introducing the inert gas at a rate of 5-10 mL / min, heating to 1200-1500 DEG C at a rate of 5-10 DEG C / min and keeping for 1-3 h, and then naturally cooling to room temperature.

9. An aspartic acid-based porous hard carbon material prepared by the method of any one of claims 1-8.

10. Application of the aspartic acid-based porous hard carbon material of claim 9 in a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of hard porous carbon for sodium ion battery

    CN116199223A

  • Preparation method of low-cost hard carbon with high specific surface area and application of low-cost hard carbon in sodium-ion battery

    CN116715216A

  • Sodium battery negative electrode material prepared from rubber leftover material and preparation method and application thereof

    CN117023556A

  • Phenolic resin-based hard carbon material for sodium ion battery and preparation method and application of phenolic resin-based hard carbon material

    CN118099421A

  • Preparation method of porous hard carbon material and application of porous hard carbon material in sodium-ion battery

    CN118239472A